A novel experimental model of Cryptococcus neoformans‐related immune reconstitution inflammatory syndrome (IRIS) provides insights into pathogenesis. Issue 12 (12th October 2015) - Eschke, Maria; Piehler, Daniel; Schulze, Bianca; Richter, Tina; Grahnert, Andreas; Protschka, Martina; Müller, Uwe; Köhler, Gabriele; Höfling, Corinna; Rossner, Steffen; Alber, Gottfried
Abstract : Antiretroviral therapy (ART) has yielded major advances in fighting the HIV pandemic by restoring protective immunity. However, a significant proportion of HIV patients co‐infected with the opportunistic fungal pathogen Cryptococcus neoformans paradoxically develops a life‐threatening immune reconstitution inflammatory syndrome (IRIS) during antiretroviral therapy. Despite several clinical studies, the underlying pathomecha‐nisms are poorly understood. Here, we present the first mouse model of cryptococcal IRIS that allows for a detailed analysis of disease development. Lymphocyte‐deficient RAG‐1 −/− mice are infected with C. neoformans and 4 weeks later adoptively transferred with purified CD4 + T cells. Reconstitution of CD4 + T cells is sufficient to induce a severe inflammatory disease similar to clinical IRIS in C. neoformans ‐infected RAG‐1 −/− mice of different genetic backgrounds and immunological phenotypes (i.e. C57BL/6 and BALB/c). Multiorgan inflammation is accompanied by a systemic release of distinct proinflammatory cytokines, i.e. IFN‐γ, IL‐6, and TNF‐α. IRIS development is characterized by infection‐dependent activation of donor CD4 + T cells, which are the source of IFN‐γ. Interestingly, IFN‐γ‐mediated effects are not required for disease induction. Taken together, this novel mouse model of cryptococcal IRIS provides a useful tool to verify potential mechanisms of pathogenesis, revealing targets for diagnosis and therapeutic interventions.